Rapidly progressive tetraplegia and cognitive deterioration during rehabilitation: A case of neurodegenerative disease - İkbali Afşar, Sevgi; Umit Yemişçi, Oya (Journal of Surgery and Medicine, 2019)
Human prion diseases are fatal, progressive neurodegenerative disorders caused by neurolytic pathogen proteins, called prions. The most common human prion disease is sporadic Creutzfeldt-Jakob disease, with an approximate annual prevalence of 0.5-1 per million. The symptoms and signs include rapidly progressive dementia, ataxia, myoclonic seizures, akinetic mutism and other neurological and neurobehavioral disorders. The clinical spectrum of Creutzfeldt-Jakob disease is highly variable; therefore it can be difficult to diagnose premortem. This article describes a 78-year-old woman who initially presented with difficulty walking and balance disorder. As a result of the evaluation, the patient was transferred to rehabilitation clinic, with a diagnosis of cervical spinal stenosis. During hospitalization, she showed progressive decline in gait and balance and deteriorated rapidly. The patient was considered to be probable sporadic Creutzfeldt-Jakob disease after further investigations.